Peranan Wahyu Illahi dalam Kanonisasi Alkitab bagi Kehidupan Orang Percaya di Era Millenial - Angelina, Yunike; Suhadi, Suhadi (Pusat Studi Pentakosta Indonesia, 2025)
The discussion of the canonization of the Bible is an interesting and relevant topic to discuss. There are pros and cons but also not a few parties who are against it according to their respective proofs. Despite the many theories circulating so far, the main factor that has led to the discussion of the canonization of the Bible has become an interesting topic to talk about even today is the question of whether the source of the writing of the Bible and the process of the canon itself is true from divine revelation or is it just a story of human experience. However, more than just a discussion of the canonization of the Bible, it is also necessary to know the role of the divine revelation in the canonization of the Bible for the lives of believers in the millennial era. The purpose of this article is to emphasize that in addition to being useful for the canonization of the Bible, divine revelation also has a role in the lives of believers in the millennial era. This research uses qualitative methods, especially literature studies. By looking at the events that are happening in society, especially the community of young people, about the role and what the real meaning of the canonization of the Bible has for their lives in this Millennial Era, researchers try to research this matter by finding out the truth from accurate and reliable reference sources so that they can produce a correct understanding of this topic. The purpose or result of this study is to inform that divine revelation also has a role in the lives of believers, especially in this Millennial Era. Believers in this Millennial Era can receive and experience divine revelation when they read and meditate on God's word (the Bible).AbstrakPembahasan mengenai kanonisasi Alkitab menjadi topik yang menarik dan relevan untuk diperbincangkan. Ada pihak-pihak yang pro tapi juga tak sedikit pihak yang kontra dengan hal tersebut sesuai dengan pembuktian mereka masing-masing. Terlepas dari banyaknya teori yang beredar selama ini, faktor utama yang menyebabkan pembahasan mengenai kanonisasi Alkitab menjadi topik yang menarik untuk dibicarakan bahkan pada masa kini adalah karena pertanyaan mengenai sumber penulisan Alkitab dan proses kanon itu sendiri apakah benar dari wahyu Ilahi atau hanya sebatas cerita pengalaman dari manusia semata. Namun, lebih dari sekedar pembahasan mengenai kanonisasi Alkitab, perlu mengetahui juga peranan dari wahyu Illahi tersebut dalam kanonisasi Alkitab bagi kehidupan orang percaya di era milenial. Tujuan dari penulisan ini untuk menekankan bahwa selain berguna untuk kanonisasi Alkitab, wahyu Illahi juga memiliki peranan bagi kehidupan orang percaya di era milenial. Penelitian ini menggunakan metode kualitatif khususnya studi pustaka. Dengan melihat peristiwa yang terjadi di masyarakat terutama komunitas anak-anak muda tentang peran dan apa makna sesungguhnya dari kanonisasi Alkitab bagi kehidupan mereka di Era Milenial ini, peneliti mencoba untuk meneliti hal ini dengan mencari tahu kebenarannya dari sumber referensi yang akurat dan terpercaya sehingga mampu menghasilkan sebuah pemahaman yang benar mengenai topik ini. Tujuan atau hasil dari penelitian ini adalah untuk memberitahukan bahwa wahyu Illahi juga memiliki peranan bagi kehidupan orang percaya terutama di Era Milenial ini. Orang percaya di Era Milenial ini dapat menerima dan mengalami wahyu Illahi ketika mereka membaca dan merenungkan firman Tuhan (Alkitab).